2011
DOI: 10.1007/s00382-011-1088-z
|View full text |Cite
|
Sign up to set email alerts
|

Possible connection between summer tropical cyclone frequency and spring Arctic Oscillation over East Asia

Abstract: This study shows that the frequency of summer tropical cyclones (TCs) in the areas of Japan, Korea, and Taiwan (JKT), which are located in the middle latitudes of East Asia, has a positive correlation with the Arctic Oscillation (AO) occurring during the preceding spring, while summer TC frequency in the Philippines (PH), located in the low latitudes, has a negative correlation with the AO of the preceding spring. During a positive AO phase, when the anomalous anticyclone forms over the mid-latitudes of East A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…Lim and Schubert (2011) revealed that both winter mean temperature anomalies and the number of days of extreme cold in the southeastern United States are closely linked to variations in AO especially in the recent past . Choi et al (2012) showed that the frequency of summer tropical cyclones in Japan, Korea, and Taiwan in the middle latitudes of East Asia, has a positive correlation with AO occurring during the preceding spring, while summer tropical cyclone frequency in the Philippines, located in the low latitudes, has a negative correlation with the AO of the preceding spring. Park et al (2011) studied changes in the characteristics of cold surges over East Asia associated with the AO and found that the blocking type of cold surge tends to occur during negative AO periods.…”
Section: Correlations With Aa and Aao Indicesmentioning
confidence: 99%
“…Lim and Schubert (2011) revealed that both winter mean temperature anomalies and the number of days of extreme cold in the southeastern United States are closely linked to variations in AO especially in the recent past . Choi et al (2012) showed that the frequency of summer tropical cyclones in Japan, Korea, and Taiwan in the middle latitudes of East Asia, has a positive correlation with AO occurring during the preceding spring, while summer tropical cyclone frequency in the Philippines, located in the low latitudes, has a negative correlation with the AO of the preceding spring. Park et al (2011) studied changes in the characteristics of cold surges over East Asia associated with the AO and found that the blocking type of cold surge tends to occur during negative AO periods.…”
Section: Correlations With Aa and Aao Indicesmentioning
confidence: 99%
“…Although sprung from the polar regions, more and more studies have indicated that the AO and AAO can affect climate variability in remote, subtropical regions (e.g. Wang and Fan, 2005;Choi et al, 2012); it would be reasonable to have these two indices in the list. To account for possible transoceanic interactions addressed by some studies (Hong et al, 2014b), the NAO index, referred to as the meridional seesaw of the SLP field with the northern and southern centres near Iceland and the Azores, respectively, is also included.…”
Section: Streamflow Data Teleconnection Indices and Other Data Setsmentioning
confidence: 99%
“…Wang et al, 2000;Yang et al, 2002;Wang and Fan, 2005;Choi et al, 2012) have investigated the various effects of teleconnection patterns on East Asian regions. The main motivation for our work thus comprises two primary objectives:…”
mentioning
confidence: 99%
“…A number of studies have reported that the AO could exert a significant impact on climate anomalies over the NH extratropics (e.g. Gong et al, 2001;Gong and Ho, 2002;Wu and Wang, 2002;Gong and Ho, 2003;Chen et al, 2005;Jeong and Ho, 2005;Wu et al, 2006;Chen and Li, 2007;Gong et al, 2011;Yang, 2011;Park et al, 2011;Cheung et al, 2012;Choi et al, 2012;Kim and Ahn, 2012;Woo et al, 2012;Chen et al, 2013aChen et al, , 2013dChoi et al, 2013). For example, Jeong and Ho (2005) showed that the frequency of the wintertime cold surge occurrence over East Asia is relatively higher during the negative AO phase than * Correspondence to: W. Chen, Center for Monsoon System Research, Institute of Atmospheric Physics Chinese Academy of Sciences, Beijing 100190, China.…”
Section: Introductionmentioning
confidence: 96%
“…Gong et al (2011) reported that springtime AO could exert influences on the following East Asian summer monsoon variability via modulating the summer western North Pacific subtropical high. Choi et al (2012) found that spring AO can impact the frequency of the following summer tropical cyclones over middle latitudes of East Asia through modulating large-scale atmospheric circulation.…”
Section: Introductionmentioning
confidence: 98%